Religious Discourse on Television - Arouche, Ines Maria Pacheco (The ESPecialist, 2012)
The purpose of this study is to analyse the process of discursive construction in a television debate involving the participation of followers of different branches of evangelic religions. The theoretical line in which this analysis is situated is Discourse Analysis of French orientation, in the segment linked to Enunciation Theory. Based on the selected corpus, we aimed at demonstrating that the reported speech and the TV reports may have an identical function in the articulation of the discursive scene that is installed in the programme.